Energy Regulation and Legislative Development in the State Duma of Russia: A Spatial Analysis of Roll Call Votes with the Optimal Classification Model, Russia 1994-2003 - Theocharis N. Grigoriadis; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
This paper investigates the role of the State Duma of Russia in energy regulation between 1994 and 2003. We applying Poole's optimal classification model of roll call votes using an ordered probit model to show impact of partisan, bureaucratic, social and economic determinants on energy law reform in the first decade of Russia's democratic transition. Our findings suggest that reforms strongly depend on negotiations, compromises and interest equilibrations. The cohesion and accountability of Russian political parties cannot be explained in terms of ideology; the traditional Left-Right axis does not hold in Russian legislative politics. Thus, our results suggest that Russia's executive federalism and the personal interests of powerful parliamentary actors have the lead in developing competitive market structures in oil, gas and electricity markets. The paradoxical conclusion is that in this turbulent institutional setting State Duma functions as a de facto regulator by contributing to economic transparency and advancing energy law reform under conditions of democratic representation and political competition.
Keywords: Q40; D72; K23; P27; P37; P31; R11; 330; energy regulation; energy roll law reform; roll call votes; legislative politics; State Duma; Russia